MRI assessment of the postprandial gastrointestinal motility and peptide response in healthy humans - Khalaf, Asseel; Hoad, Caroline; Menys, Alex; Nowak, Adam; Taylor, Stuart A.; Paparo, Stephen; Lingaya, Melanie; Falcone, Yirga; Singh, Gulzar; Spiller, Robin C.; Gowland, Penny A.; Marciani, Luca; et al. (Wiley, 2018)
Background: Feeding triggers inter-related gastrointestinal (GI) motor, peptide and appetite responses. These are rarely studied together due to methodological limitations. Recent MRI advances allow pan-intestinal, non-invasive assessment of motility in the undisturbed gut. This study aimed to develop a methodology to assess pan-intestinal motility and transit in a single session using MRI and compare imaging findings to GI peptide responses to a test meal and symptoms in a healthy volunteer cohort.